RM360 million allocated for dredging of Sarawak River - Joseph, Daryl (New Sarawak Tribune, 2016)
KUCHING: A sum of RM360 million had been confirmed by Deputy Chief Minister Tan Sri Datuk Amar Dr. Tames Jemut Masing, the Minister of Infrastructure Development and Transport for the dredging of the Sarawak River which is to commence in 2017.